PEMBINAAN MANAJEMEN KEUANGAN BAGI PENGURUS PAGUYUBAN ARGAPURI JABOTABEK DALAM MEMAKSIMALKAN PENDAPATAN SISA HASIL USAHA - Akbar, Akhmad; Supatmin, Supatmin; Sutiman, Sutiman (Yayasan Education and Social Center, 2024)
The above community service activities focus on implementing a financial management development program for the administrators of the Jabotabek Argapuri Community Association to maximize residual business income. Before the start of this program, organizations faced various challenges in financial management, including a lack of understanding of basic financial management concepts, insufficient skills in managing cash flow, creating accurate financial reports, and obstacles in increasing organizational revenue. Awareness of the importance of effective financial management for the sustainability and growth of Paguyuban is the main trigger for implementing this coaching program. The coaching program significantly contributed to increasing the residual income from the Paguyuban's business. Through effective financial management practices and revenue development strategies, the administrators succeeded in increasing the overall revenue of the organization. This improvement not only reflects better financial performance, but also provides concrete evidence of the management's ability to implement the strategies learned. Overall, this coaching program not only aims to improve individual skills, but also plays an important role in improving the welfare of organizations and society as a whole